Renal Lymphangiectasia in the Transplanted Kidney: Case Series and Literature Review. Issue 1 (January 2020) - Dawidek, Mark T.; Aquil, Shahid; Alogaili, Rafid; Gabril, Manal; Moussa, Madeleine; Sener, Alp; Luke, Patrick P.
Abstract : Background: Renal lymphangiectasia is a rare and poorly understood lymphatic disease associated with lymphatic dilation and leakage. To our knowledge, no cases have been described in the context of a transplanted kidney. Methods: We describe 2 cases of renal lymphangiectasia in transplanted kidneys, both from pediatric donors. Results: The cases of allograft lymphangiectasia are characterized by severe, symptomatic ascites refractory to attempts at medical and surgical management, and ultimately requiring allograft nephrectomy. Conclusions: While lymphatic complications, particularly lymphoceles, are not uncommon in renal transplantation, lymphangiectasia is a distinct condition which should be considered in renal transplant patients with ascites, after all other sources have been ruled out.